Observing the morphology of single-layered embedded silicon nanocrystals by using temperature-stable TEM membranes - Gutsch, Sebastian; Hiller, Daniel; Laube, Jan; Zacharias, Margit; Kübel, Christian (Beilstein Journal of Nanotechnology, 2015)
We use high-temperature-stable silicon nitride membranes to investigate single layers of silicon nanocrystal ensembles by energy filtered transmission electron microscopy. The silicon nanocrystals are prepared from the precipitation of a silicon-rich oxynitride layer sandwiched between two SiO2 diffusion barriers and subjected to a high-temperature annealing. We find that such single layers are very sensitive to the annealing parameters and may lead to a significant loss of excess silicon. In addition, these ultrathin layers suffer from significant electron beam damage that needs to be minimized in order to image the pristine sample morphology. Finally we demonstrate how the silicon nanocrystal size distribution develops from a broad to a narrow log-normal distribution, when the initial precipitation layer thickness and stoichiometry are below a critical value.
Keywords: electron irradiation damage; energy-filtered transmission electron microscopy; membrane; plane view; silicon nanocrystals; size control; size distribution